Strategi Reading Aloud dalam Menumbuhkan Minat Membaca Peserta Didik Kelas III UPT SD Negeri 5 Turatea - Dian Rahmadani; H. Yuddin Pasiri; Akbar Avicenna (Lembaga Pengembangan Kinerja Dosen, 2024)
The main problem in this study is how the Reading Aloud strategy in fostering Reading Interest in Class III UPT SD Negeri 5 Turatea. This study aims to foster interest in reading through the reading aloud strategy of class III students of UPT SD Negeri 5 Turatea. The type of research used is descriptive qualitative research. Instruments in data collection are interviews, observation sheets and documentation tools and materials. Data collection techniques using observation, interviews and documentation. The results showed that the Reading Aloud Strategy is effective for motivating students, using interesting reading techniques for students by using voice intonation and facial expressions that match the story. The implementation of the Reading Aloud strategy is able to foster students' interest in reading, they feel happy to be seen from their enthusiasm when involved in reading.